Numerical simulations of fluid flows and heat transfer in melt pools of Directed Energy Deposition of SS316L - Saldi Zaki; Pasang Tim; Khogres Winston; Budiman Arief; Gunawan Fergyanto (E3S Web of Conferences, 2024)
This paper presents the numerical model developed to simulate fluid flow and heat transfer in melt pools formed in Directed Energy Deposition of stainless steel SS316L. The model incorporated important heat and momentum source terms. The energy source terms included laser energy, latent heat of phase change, convective heat loss, radiative heat loss, evaporative heat loss, and energy addition due to molten particle deposition into the melt pool. The momentum source terms were due to surface tension effect, thermocapillary (Marangoni) effect, thermal buoyancy, momentum damping due to phase change, molten particle momentum, and recoil effect due to evaporation. The simulations suggested that the predicted flow and heat transfer in the melt pool affected the resulting shape and size. With the process parameters currently employed, the melt pool was elongated, wide and shallow, with depressed free surface and outward convective flow. The outward flow was caused by the dominant region of high temperature in the centre of the melt pool, such that the temperature gradient of surface tension is negative.